2018
DOI: 10.1016/j.jinorgbio.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-masked iron prochelators: Effects on cell death, proliferation, and hemoglobin production

Abstract: The iron metabolism of malignant cells, which is altered to ensure higher acquisition and utilization, motivates the investigation of iron chelation strategies in cancer treatment. In a prochelation approach aimed at increasing intracellular specificity, disulfide reduction/activation switches are incorporated on iron-binding scaffolds resulting in intracellularly activated scavengers. Herein, this strategy is applied to several tridentate donor sets including thiosemicarbazones, aroylhydrazones and semicarbaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 74 publications
(90 reference statements)
3
27
0
Order By: Relevance
“…According to our previous observation that tumor-associated MΦ adopt an iron releasing phenotype ( Figure 3D), we further established an in vitro setting to analyze the role of macrophagesecreted iron in conferring renal tumor cell growth ( Figure 5A). As previously published [41,42], IL-10 stimulation of primary human MΦ induced the release of iron into the supernatant measured by AAS ( Figure 5B). We next applied macrophage-conditioned supernatants to renal tumor cells CAKI-1 (Figure 5C,E) and 786-O ( Figure 5D,F) and observed enhanced proliferation ( Figure 5C,D) as well as tumor cell migration (Figure 5E,F) measured by xCELLigence in real-time upon stimulation with IL-10-conditioned media.…”
Section: Tumor Proliferation By Macrophage-secreted Iron Is Suppressesupporting
confidence: 83%
See 2 more Smart Citations
“…According to our previous observation that tumor-associated MΦ adopt an iron releasing phenotype ( Figure 3D), we further established an in vitro setting to analyze the role of macrophagesecreted iron in conferring renal tumor cell growth ( Figure 5A). As previously published [41,42], IL-10 stimulation of primary human MΦ induced the release of iron into the supernatant measured by AAS ( Figure 5B). We next applied macrophage-conditioned supernatants to renal tumor cells CAKI-1 (Figure 5C,E) and 786-O ( Figure 5D,F) and observed enhanced proliferation ( Figure 5C,D) as well as tumor cell migration (Figure 5E,F) measured by xCELLigence in real-time upon stimulation with IL-10-conditioned media.…”
Section: Tumor Proliferation By Macrophage-secreted Iron Is Suppressesupporting
confidence: 83%
“…Macrophage iron homeostasis is functionally coupled to their heterogeneity and plasticity, with their polarization status being reflected also by their expression profiles of iron-regulated genes. We previously showed that treatment of MΦ with LPS/IFNγ enhanced the retention of iron within the cell, whereas stimulation with anti-inflammatory cytokines such as IL-10 or IL-4 induced the release of iron [41]. This observation falls in line with a typical cytokine/chemokine profile of differentially polarized MΦ.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This difference in activity likely arises from electronic differences between the phenyl vs. methyl substituents of BSPTH vs BSMTH, something that has been observed in disulfide-bridged prochelators built on a similar scaffold. 31,43 Interestingly, the disulfide prochelators introduced by Tomat and coworkers are reductively-activated and create S,N,S or S,N,O iron chelators with interesting antiproliferative activity against cancer cells. 12,43 The boronate prochelators discussed here, on the other hand, are oxidatively activated and create O,N,O coordination spheres.…”
Section: Discussionmentioning
confidence: 99%
“…31,43 Interestingly, the disulfide prochelators introduced by Tomat and coworkers are reductively-activated and create S,N,S or S,N,O iron chelators with interesting antiproliferative activity against cancer cells. 12,43 The boronate prochelators discussed here, on the other hand, are oxidatively activated and create O,N,O coordination spheres. The combination of these two approaches reveals the opportunity available to tune prochelators for desirable biological applications by adjusting their coordination sphere, activation mechanism and stability.…”
Section: Discussionmentioning
confidence: 99%